Recent developments among world’s leading generic markets - Jakovljevic, Mihajlo B (Medicinski časopis, 2014)
Possible net savings achievable via generic substitution of brand name drugs could reach even € 30 billion within EU’s disposable health care expenditure. Seemingly this trend could could be recognized in world major national pharmaceutical markets, the US and Japan, as well as among major emerging economies such as Brasil, Russia, India and China. Different policy strategies in order to stimulate generic medicines prescription, dispensing and sales have been deployed in these countries over the course of past three decades with variable success rates. This contribution should provide short overview of current trends in these pharmaceutical markets.